Thermal analysis, X-ray diffraction, spectroscopy studies and magnetic properties of the new compound Tl2HAsO4.Te(OH)6 - Bechibani, I.; litaiem, H.; Granda, S. Garcia; Dammak, M.; Ktari, L. (JOURNAL OF ADVANCES IN CHEMISTRY, 2011)
The Tl2HAsO4.Te(OH)6 (TlAsTe) compound crystallizes in the triclinic system P1 with unit cell parameters: a= 7.100(10) Ã…, b= 7.281(13) Ã…, c= 8.383(11) Ã…, Î±= 76.91(1)Â°, Î²= 87.16(1)Â°, Î³= 66.96(2)Â°, Z= 2 and V= 388.19(1) Ã…3. This new structure can be described as a lamellar one with the atomic arrangement being built by planes of Te(OH)6 octahedra alterning with planes of arsenate tetrahedra. Raman and infrared spectra recorded at room temperature confirm the presence of As Â and Te Â groups and characterize the hydrogen bonds present in the crystal lattice. Differential scanning calorimerty shows the presence of three-phase transitions at 396 K, 408 K and 430 K present in the title compound. Typical thermal analyses, such as differential thermal analysis and thermogravimetry show that the decomposition of this material starts at about T= 445 K. Magnetization curve of Tl2HAsO4Â·Te(OH)6 substance have revealed a diamagnetic response overall temperature range studied.